The Influence of Self Help Group to Family Anxiety Levels in Caring Mental Disorder Patients - Dwi Heppy Rochmawati; Betie Febriana; Andi Prasetyo (Indonesian Journal of Global Health Research, 2020)
Families who provide care to family members who have mental disorders experience a psychological condition that is anxiety. Anxiety can decrease or decrease with self-help therapy groups. In this study, families are gathered and formed groups to exchange experiences. Objective: this study describes the results of the implementation of self help group therapy on the level of anxiety of families with mental patients. This study used a quasy experiment design with pre and post test methods without control groups, meaning that data collection was carried out before and after the intervention by giving theraphy self help group. Self Help Group Therapy is a group of two or more people who have the desire to share problems, help each other with things that are experienced or are the focus of attention aimed at overcoming mental disorders and improving cognitive and emotional abilities so as to achieve feelings of well-being. total sampling. Most respondents aged 45-55 years (42%), most education graduated from elementary school (46%) and most jobs (48%). The anxiety most experienced by the family before therapy was moderate anxiety (42%) and after attending anxiety therapy the majority of respondents became mild anxiety (38%). There is an effect of theraphy self help group on the level of family anxiety by using the dependent sample test obtained p value 0,000 (<0.05).